Evaluación y mitigación de factores abióticos en plantas de tomate (Solanum lycopersicum) por B. amyloliquefaciens aisladas de un ambiente semiárido de la Guajira (2022)
Tomato (Solanum lycopersicum) is considered one of the main vegetables in the world, thanks to its nutritional content. Due to climate change, tomato crops, like others, are potentially exposed to abiotic factors that have a negative effect on their productivity. In this work, the ability of B. amyloliquefaciens to promote plant growth of tomato exposed to salinity (0, 50, 100 and 150 mM) and stress by metals such as Cadmium, Cobalt, and Nickel at concentrations of 5 and 10 mM was evaluated. The results showed that plants with and without inoculum were affected at high salt concentrations (100 and 150 mM), with low values in fresh and dry weight variables of stem and root, compared to control plants without salinity. In the metals assay, it was observed that the presence of metals favored the growth of plants without inoculum